2015
DOI: 10.3109/15412555.2014.993465
|View full text |Cite
|
Sign up to set email alerts
|

Phrenic Nerve Conduction Abnormalities Correlate with Diaphragmatic Descent in Chronic Obstructive Pulmonary Disease

Abstract: Phrenic nerve conduction abnormality is an appreciated finding in COPD. Nerve stretching associated with diaphragmatic descent can be a suggested mechanism for nerve lesion. The presence of phrenic neuropathy may be an additional contributing factor to diaphragmatic dysfunction in COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…The rate of detectable myosin decreases, resulting in altered sarcomeric organization and further decreasing of the contractile strength [6]. The phrenic activity is abnormal, presumably due to the nerve stretching caused by the chronic lowering of the diaphragm, resulting in such a neuropathy [7]. The exercise intolerance in patients with COPD does not correlate with the common functional index (forced expiratory volume in 1 second -FEV1); rather it is the peripheral muscle adaptation, including that of the diaphragm, to have a heavy influence on the symptomatic scenario [8,9] (Figures 1 and 2).…”
Section: Adaptation Of the Diaphragm In Patients Affected By Copdmentioning
confidence: 99%
“…The rate of detectable myosin decreases, resulting in altered sarcomeric organization and further decreasing of the contractile strength [6]. The phrenic activity is abnormal, presumably due to the nerve stretching caused by the chronic lowering of the diaphragm, resulting in such a neuropathy [7]. The exercise intolerance in patients with COPD does not correlate with the common functional index (forced expiratory volume in 1 second -FEV1); rather it is the peripheral muscle adaptation, including that of the diaphragm, to have a heavy influence on the symptomatic scenario [8,9] (Figures 1 and 2).…”
Section: Adaptation Of the Diaphragm In Patients Affected By Copdmentioning
confidence: 99%
“…Hopkinson et al 14 did not find any significant difference between nine COPD patients and seven controls, Lu et al 15 studied only three COPD patients and found reduced CMAP amplitudes in two of them. El-Tantawi et al 16 studied 40 COPD patients (all men) and compared them with 27 matched age and height controls. He did not find any significant difference between these two groups in amplitude and the latency of phrenic CMAP (area and duration were not mentioned) using the same recording points that were used by Podnar and Harlander 7 and ourselves.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hamed et al [21] reported bilateral increase in CMEPL and CMCT in their studied COPD compared to healthy control group as well as decreased DRMT. Further, El-Tantawi et al [22] found peripheral phrenic nerve conduction abnormalities in 42.5% of their studied COPD patients that did not correlate with disease severity. These results are in accordance of the current results and could be explained by increased excitation of motor cortex and corticospinal pathways to the respiratory muscles in the COPD patient [23] and less excitability of intracortical facilitatory circuits at long interstimulus intervals using paired stimulation denoting ceiling effect of motor control output to the respiratory muscles of case of COPD.…”
Section: Discussionmentioning
confidence: 94%